2000
DOI: 10.1074/jbc.m006274200
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-dependent Protein Kinase Phosphorylation of EVL, a Mena/VASP Relative, Regulates Its Interaction with Actin and SH3 Domains

Abstract: Proteins of the Ena/VASP family are implicated in processes that require dynamic actin remodeling such as axon guidance and platelet activation. In this work, we explored some of the pathways that likely regulate actin dynamics in part via EVL (Ena/VASP-like protein). Two isoforms, EVL and EVL-I, were highly expressed in hematopoietic cells of thymus and spleen. In CD3-activated T-cells, EVL was found in F-actin-rich patches and at the distal tips of the microspikes that formed on the activated side of the T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
216
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 170 publications
(233 citation statements)
references
References 60 publications
14
216
2
1
Order By: Relevance
“…Other candidate PKA targets likely to be regulated during axon guidance include members of the Enabled (Ena)/ Vasodilator-stimulated phosphoprotein (VASP) family, which have been implicated in the regulation of actin-based motility. In particular, the Ena/VASP-like protein binds its ligands in a manner that depends on PKA phosphorylation (Lambrechts et al, 2000). It remains to be determined whether any members of the Rho GTPases and Ena/VASP are the direct targets of protein kinase A during PACAP-induced attraction.…”
Section: Discussionmentioning
confidence: 99%
“…Other candidate PKA targets likely to be regulated during axon guidance include members of the Enabled (Ena)/ Vasodilator-stimulated phosphoprotein (VASP) family, which have been implicated in the regulation of actin-based motility. In particular, the Ena/VASP-like protein binds its ligands in a manner that depends on PKA phosphorylation (Lambrechts et al, 2000). It remains to be determined whether any members of the Rho GTPases and Ena/VASP are the direct targets of protein kinase A during PACAP-induced attraction.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of VASP negatively regulates actin nucleation/G-actin binding and interaction with F-actin and some cell adhesion regulators [48][49][50]. On the other hand, VASP binding to focal adhesion protein and profilin, a regulator of actin polymerization, are independent of the VASP phosphorylation status [48,51].…”
Section: Udp-induced Vasp Phosphorylation At Ser157 Is Mediated By Rhmentioning
confidence: 99%
“…The effect of SNP and L-arginine on PKG II activity was confirmed by detecting the phosphorylation of VASP, the serine/threonine residues of which are substrates for the PKA and PKG (24). There are three phosphorylation sites of VASP, namely Ser157, Ser239 and Tyr278 (13,(25)(26)(27). Tao et al (13) reported that Ser239 was a key phosphorylation site of VASP for PKG II activation.…”
Section: Discussionmentioning
confidence: 99%